2016
DOI: 10.3747/co.23.3110
|View full text |Cite
|
Sign up to set email alerts
|

Report on a Delphi Process and Workshop to Improve Accrual to Cancer Clinical Trials

Abstract: Cancer clinical trials (ccts) are essential for furthering knowledge and developing effective interventions to improve the lives of people living with cancer in Canada. Randomized controlled trials are particularly important for developing evidence-based health care interventions. To produce robust and relevant research conclusions, timely and sufficient accrual to ccts is essential.The present report delivers the key recommendations emerging from a workshop meeting, Improve Accrual to Cancer Clinical Trials, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…However, less than 5% of adult patients with cancer participate in CTs [ 1 ] and many trials suffer from insufficient accrual, with earlier phase trial being especially problematic [ 2 ]. Poor accrual and retention have been linked to complex and lengthy consent procedures, which may create difficulties for patients in providing informed consent [ 3 , 4 ]. A systematic review evaluating patient understanding of consent for participation in CTs concluded that patients often do not fully understand the potential health risks of novel experimental drugs and have unrealistic expectations of benefit [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, less than 5% of adult patients with cancer participate in CTs [ 1 ] and many trials suffer from insufficient accrual, with earlier phase trial being especially problematic [ 2 ]. Poor accrual and retention have been linked to complex and lengthy consent procedures, which may create difficulties for patients in providing informed consent [ 3 , 4 ]. A systematic review evaluating patient understanding of consent for participation in CTs concluded that patients often do not fully understand the potential health risks of novel experimental drugs and have unrealistic expectations of benefit [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…36 To address the structural issue of limited time and CT resources, a recent report identified the need for streamlined accrual strategies and trials designed to balance feasibility, accessibility, and scientific opportunity. 37 For example, pragmatic CTs that compare effectiveness of treatment alternatives in real-world settings and include representation from diverse patient populations have been one trial design proposed to simplify and improve the accrual process. 27,38 Streamlining written informed consent documents has also become a focus of global effort to ensure more meaningful and efficient consent procedures within trials.…”
mentioning
confidence: 99%